Cumulative Lead Exposure and Age-related Hearing Loss: The VA Normative Aging Study - Park, Sung Kyun (2010)
Although lead has been associated with hearing loss in occupational settings and in children, little epidemiologic research has been conducted on the impact of cumulative lead exposure on age-related hearing loss in the general population. We determined whether bone lead levels, a marker of cumulative lead exposure, are associated with decreased hearing ability in 448 men from the Normative Aging Study, seen between 1962 and 1996 (2,264 total observations). Air conduction hearing thresholds were measured at 0.25 to 8 kHz and pure tone averages (PTA) (mean of 0.5, 1, 2 and 4 kHz) were computed. Tibia and patella lead levels were measured using K x-ray fluorescence between 1991 and 1996. In cross-sectional analyses, after adjusting for potential confounders including occupational noise, patella lead levels were significantly associated with poorer hearing thresholds at 2, 3, 4, 6 and 8 kHz and PTA. The odds of hearing loss significantly increased with patella lead levels. We also found significant positive associations between tibia lead and the rate change in hearing thresholds at 1, 2, and 8 kHz and PTA in longitudinal analyses. Our results suggest that chronic low-level lead exposure may be an important risk factor for age-related hearing loss and reduction of lead exposure could help prevent or delay development of age-related hearing loss.